On the Sociality and Immersiveness of the Introspective Encounter - Rodax, Natalie (Integrative psychological & behavioral science, 2021)
Scientifically accessing and systematically approaching self-reports and a research subject’s reflection is a central task of psychological research. However, psychological research often fails to account for the sociality of the individual’s self-reports and reflection. In fact, addressing the complexity of the multi-faced reciprocal relations, how individuals get in touch with themselves through the encounter with the ‘other’ occupies psychology since its beginning up to the present day. A recently published volume edited by Gobodo-Madikizela ( 2021 ) delivers an in-depth analysis of the mutual encounters of second-generation descendants of perpetrators and survivors of the Holocaust and stresses the importance of “engaging with the past through second generation dialogue”, showing that the introspective, dialogical encounter offers fruitful insight to processes that frequently remain ‘invisible’ and under the surface of intergenerationally travelling trauma, shame and guilt. Using the example of Gobodo-Madikizela’s volume ( 2021 ), this article seeks to highlight contemporary applications of the introspectiv encounter and shows its value for locating psychology beyond a strict natural scientific discipline-understanding. By developing the notion of the introspective encounter ‘of the first and the second degree’, this article aims at showing how Gobodo-Madikizela’s volume immerses readers, not only showing how psychology can produce a scientific outcome by crossing the border of the classic subject-object separation (first degree), but also facilitating the reader to enter an introspective dialogue with herself (second degree). By this analysis, this article challenges the way we currently converse in psychological research.